The Inﬂuence of National Health Insurance Members’ Family Satisfaction on Repurchasing Intention of RSMC Hospital’s Inpatient Care Facility - Joeliaty Joeliaty; Ninuk Nurjayanti (Jurnal Bisnis Manajemen, 2018)
Hospital is an advanced healthcare provider for the patent of Jaminan Kesehatan Nasional (JKN) / National Health Insurance members. Providing qualified and satisfied services for all JKN members are very important to answer the negative image that lays within the community about the poor quality of services towards JKN member patent. RumahSakit Mata Cicendo (RSMC) or Cicendo Eyes Hospital-Bandung is a national health referral hospital in Indonesia. JKN members put a very high expectation regarding RSMC service quality level. Therefore, studying the JKN member patents’ family satisfaction which leads to health care service repurchasing intention is very important to be conducted. The current study is aimed to picture and analyze the correlation between JKN member patents’ family satisfactionlevel, and repurchasing intention towards RSMC service. This quantitative study is conducted at RSMC Bandung in December 2016. Based on Slovin formula, the study samples generated are 91  respondents. The research finds that both satisfaction and service repurchasing intention are high. In addition, path analysis with SPSS v23 shows that health care service satisfaction level positively inﬂuence repurchasing intention at about 75,3%.